2015
DOI: 10.1002/acr.22523
|View full text |Cite
|
Sign up to set email alerts
|

Direct Hospital Cost Determinants Following Hip and Knee Arthroplasty

Abstract: Objective. Total joint arthroplasty (TJA) places a significant economic burden on health care resources. This cohort study examines the costs associated with arthroplasty in 827 patients undergoing hip and knee TJA from January 2011 to June 2012 at a single center in Melbourne, Australia. Methods. Data included total inpatient, outpatient, and readmissions costs in the 30 days following TJA. Factors associated with cost were modeled using negative binomial regression and extrapolated to the Australian populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 24 publications
3
87
1
2
Order By: Relevance
“…[10][11][12][13] We used a national cohort from hospitals with high volumes of arthroplasty procedures, and the characteristics of the unmatched cohort were typical for patients who undergo TKA in Australia. 4,8,17,20,21 Our matched cohort should therefore be a representative sample of such patients. Our PS strategy achieved acceptable matching between the cohorts on many variables purported to influence treatment allocation and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] We used a national cohort from hospitals with high volumes of arthroplasty procedures, and the characteristics of the unmatched cohort were typical for patients who undergo TKA in Australia. 4,8,17,20,21 Our matched cohort should therefore be a representative sample of such patients. Our PS strategy achieved acceptable matching between the cohorts on many variables purported to influence treatment allocation and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1 This trend is consistent with those in other countries. 2,3 The procedure reduces pain, improves function, and enhances healthrelated quality of life, but is expensive; 4 TKA is often cited as a major driver of increases in private health insurance premiums. 5,6 An important but underappreciated contributor to the overall cost of TKA is post-operative care in an inpatient rehabilitation facility.…”
mentioning
confidence: 99%
“…The national expenditure associated with DVT in the United States was estimated at US$1.5 billion in 1997 . Reducing the incidence of VTE to 2% would potentially lead to a saving of US$29 million . The American Society of Clinical Oncology Clinical Practice Guidelines recommended that thromboprophylaxis be considered for selected high‐risk patients with active cancer .…”
Section: Discussionmentioning
confidence: 99%
“…39 Reducing the incidence of VTE to 2% would potentially lead to a saving of US$29 million. 40 The American Society of Clinical Oncology Clinical Practice Guidelines recommended that thromboprophylaxis be considered for selected high-risk patients with active cancer. 41 We assessed the ability of TEG to identify patients with gynecologic cancers at risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…This dramatic increase in cost was due to a combination of factors including prolonged operating time, increased blood loss, complications and length of inpatient stay. A similar study of 827 THA and TKA patients in Australia reported an increase to the cost of arthroplasty of 61% in the presence of SSI adding an estimated AUS $97 million to Total Joint Arthroplasty costs in the first 30 days following surgery [22]. …”
Section: The Incidence and Economic Burden Of Pjimentioning
confidence: 99%